The medium-term impact of a micronutrient powder intervention on anemia among young children in Rural China - Siqi Zhang; Lei Wang; Renfu Luo; Scott Rozelle; Sean Sylvia (BMC, 2024)
Abstract Background Poor development of young children is a common issue in developing countries and it is well established that iron deficiency anemia is one of the risk factors. Research has shown that iron deficiency is a common micronutrient deficiency among children in rural China and can result in anemia. A previous paper using data from the same trial as those used in the current study, but conducted when sample children were younger, found that after 6 months of providing caregivers of children 6-11 months of age free access to iron-rich micronutrient powder (MNP) increased the hemoglobin concentrations (Hb) of their children. However, no effects were found 12 and 18 months after the intervention. The current study followed up the children four years after the start of the original intervention (when the children were 4-5 years old) and aims to assess the medium-term impacts of the MNP program on the nutritional status of the sample pre-school-aged children, including their levels of Hb, the prevalence of anemia, and the dietary diversity of the diets of the children. Methods At baseline, this study sampled 1,802 children aged 6-11 months in rural Western China. The intervention lasted 18 months. In this medium-term follow-up study that successfully followed 81% (n = 1,464) of children (aged 49-65 months) from the original study population 4 years after the start of the intervention, we used both intention-to-treat (ITT) effect and average treatment on the treated effect (ATT) analyses to assess the medium-term impacts of the MNP distribution program on the nutritional status of sample children. Results The ITT analysis shows that the MNP intervention decreased the prevalence of anemia of young children in the medium run by 8% (4 percentage points, p < 0.1). The ATT analysis shows that consuming 100 (out of 540) MNP sachets during the initial intervention led to a decrease in anemia of 4% (2 percentage points, p < 0.1). Among children with moderate anemia at baseline (Hb < 100 g/L), the intervention reduced the probability of anemia by 45% (9 percentage points, p < 0.1), and, for those families that complied by consuming 100 (out of 540) sachets, a 25% (5 percentage points, p < 0.05) reduction in the anemia rate was found. The MNP intervention also led to a persistent increase in dietary diversity among children that were moderately anemic at baseline. The results from the quantile treatment effect analysis demonstrated that children with lower Hb levels at baseline benefited relatively more from the MNP intervention. Conclusions The findings of the current study reveal that the MNP intervention has medium-term effects on the nutritional status of children in rural China. The impacts of the MNP program were relatively higher for children that initially had more severe anemia levels. Hence, the implications of this study are that programs that aim to increase caregiver knowledge of nutrition and improve their feeding practices should be encouraged across rural China. Families, policymakers, and China's society overall need to continue to pay more attention to problems of childhood anemia in rural areas. This is particularly crucial for families with moderately anemic children at an early age as it can significantly contribute to improving the anemia status of children across rural areas of China. Trial registration ISRCTN44149146 (15/04/2013).